Reverse left ventricular remodeling after aortic valve replacement for aortic stenosis: a systematic review and meta-analysis - Sousa Nunes, F.; Amaral Marques, C.; Isabel Pinho, A.; Sousa-Pinto, B.; Beco, A.; Ricardo Silva, J.; Saraiva, F.; Macedo, F.; Leite-Moreira, A.; Sousa, C. (Frontiers in Cardiovascular Medicine, 2024)
Reverse left ventricular (LV) remodeling after aortic valve replacement (AVR), in patients with aortic stenosis, is well-documented as an important prognostic factor. With this systematic review and meta-analysis, we aimed to characterize the response of the unloaded LV after AVR. We searched on MEDLINE/PubMed and Web of Science for studies reporting echocardiographic findings before and at least 1 month after AVR for the treatment of aortic stenosis. In total, 1,836 studies were identified and 1,098 were screened for inclusion. The main factors of interest were structural and dynamic measures of the LV and aortic valve. We performed a random-effects meta-analysis to compute standardized mean differences (SMD) between follow-up and baseline values for each outcome. Twenty-seven studies met the eligibility criteria, yielding 11,751 patients. AVR resulted in reduced mean aortic gradient (SMD: −38.23 mmHg, 95% CI: −39.88 to −36.58, I2=92%), LV mass (SMD: −37.24 g, 95% CI: −49.31 to −25.18, I2=96%), end-diastolic LV diameter (SMD: −1.78 mm, 95% CI: −2.80 to −0.76, I2=96%), end-diastolic LV volume (SMD: −1.6 ml, 95% CI: −6.68 to 3.51, I2=91%), increased effective aortic valve area (SMD: 1.10 cm2, 95% CI: 1.01 to 1.20, I2=98%), and LV ejection fraction (SMD: 2.35%, 95% CI: 1.31 to 3.40%, I2=94.1%). Our results characterize the extent to which reverse remodeling is expected to occur after AVR. Notably, in our study, reverse remodeling was documented as soon as 1 month after AVR.